1995
DOI: 10.1177/0022427895032004004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Religion on Adolescent Delinquency Revisited

Abstract: This is a study of 1,093 adolescents who attended public high schools in rural Arkansas; Little Rock, Arkansas; or Baltimore, Maryland. The results do not support the hypothesis that antiascetic behaviors are more affected by religiosity than are criminal behaviors. Nor does the study support the theoretical hypothesis that religiosity is an antecedent factor that has effects that are fully mediated through other more proximate elements of social control. It also finds few real differences in the effects of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 44 publications
3
60
0
1
Order By: Relevance
“…These studies joined a litany of research showing an association between the perception of God or religion as important, participation in religious activities, and decreased risk behaviors, ranging from drug and alcohol abuse (Amey, Albrecht, & Miller,1996;Brownfield & Sorenson, 1991;Gorsuch, 1995;Kharari & Harmon, 1984;McBride, Mutch, & Chitwood, 1996;Miller, Davies, & Greenwald, 2000), to juvenile delinquency (Benda, 1995;Benda & Corwyn, 2001;Cochran, 1989;Stark, Kent, & Doyle, 1982;Roehlkepartain, King, Wagener & Benson, 2006). For example, one study of 8,165 youth in the fifth through ninth grades showed a positive correlation between youth's pro-social behavior and connections to church and religion.…”
mentioning
confidence: 99%
“…These studies joined a litany of research showing an association between the perception of God or religion as important, participation in religious activities, and decreased risk behaviors, ranging from drug and alcohol abuse (Amey, Albrecht, & Miller,1996;Brownfield & Sorenson, 1991;Gorsuch, 1995;Kharari & Harmon, 1984;McBride, Mutch, & Chitwood, 1996;Miller, Davies, & Greenwald, 2000), to juvenile delinquency (Benda, 1995;Benda & Corwyn, 2001;Cochran, 1989;Stark, Kent, & Doyle, 1982;Roehlkepartain, King, Wagener & Benson, 2006). For example, one study of 8,165 youth in the fifth through ninth grades showed a positive correlation between youth's pro-social behavior and connections to church and religion.…”
mentioning
confidence: 99%
“…Furrow and Wagener join a long list of scholars who have found an association between religious perception and religious participation and reduced engagement in risk behaviors ranging from drug and alcohol abuse (Gorsuch, 1995;Kharari and Harmon, 1984;McBride et al, 1996) to juvenile delinquency (Benda, 1995;Cochran, 1989;Stark et al,1982).…”
Section: Religion and Youth Behaviormentioning
confidence: 99%
“…Some researchers have documented a relationship between religious involvement and the development of delinquency (Benda, 1995;Johnson et al, 2001;Stark et al, 1982), while others assert that the relationship is nonexistent (Hirschi & Stark, 1969). Rodney Stark has been involved in two of the above cited studies with conflicting results, Hirschi and Stark (1969) where it was emphatically stated that there was no relationship and Stark et al (1982) whose findings indicated that a relationship exists.…”
Section: Religiositymentioning
confidence: 99%
“…They found that processing decisions in the juvenile justice system of several States were not racially neutral. The direct and indirect effects of race were present at various stages of processing and the effects may accumulate as processing progresses (Pope & Feyerherm, 1990a, 1990b,1995. Pope and Feyerherm (1995) provided further evidence that more than half of the juveniles incarcerated nationwide are minority youth.…”
Section: Discriminationmentioning
confidence: 99%
See 1 more Smart Citation